A STUDY ON THE TECHNIQUES AND METHODS OF THE TRANSLATION OF THE POLITICAL TEXT IN THE INTERNATIONAL POLITICAL NEWS IN PRINTED MEDIA - Suprapto Suprapto; Samiati Tarjana; Nababan Nababan (Proceeding of International Conference on Art, Language, and Culture, 2019)
This paper presents the results of the text analysis about the techniques and methods of the English-Indonesian translation of the political text in the international political news in printed media. The printed media used as the representation of the data is taken from Associated Press (AP), United Press (UPI), Reuters, Agency France Press (AFP) as the source texts. Whereas Jawa Pos, the national-printed media, and Solo Pos, the local - printed media used as the target texts.The focus of the news is about the United States as the super power country written in English, in the western-printed media news,  and the news transfered into the national and local-printed media in Indonesian language.The method used in this reseach is descriptive qualitative research with holistic criticism approach. The results show the techniques and methods of the translation of political text in the internatioanal political news in those printed media, and the ideologies of the translators in those media. What kinds of techniques and methods are used in translating the text, and what ideology is mostly used by the translators.